1994
DOI: 10.2307/1542037
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Histocompatibility and Regeneration in the Solitary Reef Coral Fungia scutaria

Abstract: Discoid coralla of the solitary free-living reef coral Fungia scutaria were cut with a rock saw and rejoined in various paired combinations and orientations of autogeneic sections (self to self), isogeneic sections (clone-mate to clone-mate), and allogeneic sections (two different genotypes). Results of these experiments provide the first evidence of histocompatibility in a solitary coral. Autogeneic or isogeneic sections of coralla with one section containing a mouth were joined along cut edges. In all cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
(24 reference statements)
5
20
0
Order By: Relevance
“…Interestingly, when the same allograft pairs were reset, the median reaction time was reduced to 12 d, implying immunological memory and specificity. The intensified reaction was marked by early hyperplasia and secretion of mucus at the tissue interfaces (Hildemann et al 1977).Similar results were later documented in a solitary reef coral, Fungia scutaria (Jokiel & Bigger 1994). Further work on self versus non-self recognition of the coral Pocillopora damicornis showed that juvenile corals of different genotypes fused, while adult branches of the same species (but again of different genotypes) did not fuse (Hidaka 1985).…”
supporting
confidence: 69%
“…Interestingly, when the same allograft pairs were reset, the median reaction time was reduced to 12 d, implying immunological memory and specificity. The intensified reaction was marked by early hyperplasia and secretion of mucus at the tissue interfaces (Hildemann et al 1977).Similar results were later documented in a solitary reef coral, Fungia scutaria (Jokiel & Bigger 1994). Further work on self versus non-self recognition of the coral Pocillopora damicornis showed that juvenile corals of different genotypes fused, while adult branches of the same species (but again of different genotypes) did not fuse (Hidaka 1985).…”
supporting
confidence: 69%
“…Corals accept isogenic (intracolony) grafts through complete fusion of tissue and skeleton , 1977a, Raison et al 1976, Bak & Criens 1982, Neigel & Avise 1983, Jokiel & Bigger 1994), but reject allogenic (intraspecies) and xenogenic (interspecies) grafts through cytotoxic interaction and necrosis (Theodor 1970, 1977a,b, 1980a,b, Raison et al 1976, Johnston et al 1981, Jokiel & Bigger 1994). This aggression is accelerated for repeat grafts, indicating the presence of specific induced alloimmune memory (Theodor 1970, Raison et al 1976, Hildemann et al 1977a, 1980a,b, Johnston et al 1981, an immune response generally reserved for vertebrates.…”
Section: Coral Cellular Defensesmentioning
confidence: 99%
“…The existence of an allorecognition system is welldocumented in adult coral species: genetically identical grafts (autografts) fuse, whereas genetically different grafts (allografts and xenografts) rarely fuse and show various histoincompatible responses (Chornesky 1991, Chadwick-Furman & Rinkevich 1994, Jokiel & Bigger 1994, Frank et al 1996.…”
Section: Introductionmentioning
confidence: 99%